ANALISIS PENGARUH CRM DAN PROMOSI TERHADAP LOYALITAS PELANGGAN XL AXIATA (STUDI PADA MAHASISWA STIE ALWASHLIYAH SIBOLGA) - Permatasari, Dina Indah; Chania, Mutia Fitri; Pane, Ira; Pasaribu, Kurnia Arifah (POLITEKNIK LP3I JAKARTA, 2026)
The purpose of this study is to determine the effect of Customer Relationship Management on XL Axiata Customer Loyalty among Students in Sibolga, to determine the effect of Promotion on XL Axiata Customer Loyalty among Students in Sibolga, and to determine the effect of Customer Relationship Management and promotion simultaneously on XL Axiata Customer Loyalty among Students in Sibolga. This study uses a quantitative description of the questionnaire instrument with a population of 1,268 student consumers in Sibolga city. The sample determination uses saturated sampling so that the research sample is 75 people. The results of the study are the t-test coefficient value of Customer Relationship Management 3.861; t-table value 1.993, so the t-test value > t-table (3.861 > 1.993); sig value < 0.05 (0.000 < 0.05), the t-test coefficient value of Promotion 4.943; t-table value 1.993, so the t-test value > t-table (4.943 > 1.993); sig value < 0.05 (0.000 < 0.05). The Fcount value of Customer Relationship Management and Promotion is 5.228 and the Ftable value is 3.219, so Fcount> Ftable (5.228> 2.731; sig value < 0.05 (0.000 < 0.05). The RSquare value is 0.698 or R2 x 100% 69.80%, meaning that the cause variable makes a large contribution to explaining XL Axiata Student Customer Loyalty in Sibolga, namely 69.80%, the remaining 31.20% is influenced by other factors.